Feeding Substitution Using Fish Waste, Papaya Leaf and Banana Peel for Kampung Chicken Production - Pagala , Muhammad Amrullah; Hafid, Harapin; Sandiah, Natsir; Aku, Achmad Selamet; Zulkarnaen, Deky; Has, Hamdan; Badaruddin, Rusli; Kurniawan, Widhi (International Journal of Poultry Science, 2019)
Background and Objective: Kampung chickens are native Indonesian chickens that have the ability to utilize the low quality of local feed. This research was aimed to study the responses of kampung chickens to local-based feedstuff. Materials and Methods: A total of 140 Tolaki strain kampung chickens (25 females and 5 males) were raised to obtain production performance. Chickens were divided into two equal groups (a group of 70 receiving local feed and a group of 70 receiving commercial feed). The local feedstuffs used in this research were yellow corn, rice bran, fish meal, banana peel meal and papaya leaf meal. The obtained data was analyzed using a t-test (Independent samples t-test). The research variables were indicators of production performance, including feed intake (FI), average daily weight gain (ADG) and feed conversion ratio (FCR). Results: Research results showed that there were highly significant correlation (p<0.01) between the body weight gain and feed consumption. However, the different feed treatments did not contribute differences (p>0.05) in FCR. Conclusion: The local feedstuff for kampung chickens could provide a benefit as a substitute for commercial feed because the local feed had a good impact on chicken production performance.